1995
DOI: 10.5144/0256-4947.1995.655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mebendazole with Metronidazole and Furazolidone in the Treatment of Giardiasis in Children

Abstract: and Furazolidone in the Treatment of Giardiasis in Children. 1995; 15(6): 655-656 Giardia lamblia is a flagellated protozoan that has adapted to being a parasite in the upper gut of a person. As a worldwide health problem, the carriage rate of giardiasis ranges between 1% and 7% in developed countries and 5% to 50% in developing countries.1 In addition to standard therapies with metronidazole and furazolidone, mebendazole has been suggested as a new agent in this field. 2 We have compared the efficacy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Al-Waili reported over 90% efficacy in two studies in children (8,9). However, other studies in both pediatric and adult populations have not shown equal success but instead have shown effectiveness in 80% (211) and in 60% or less (39,92,132; L. di Martino, A. Nocerino, and M. Pettoello Mantovani, Letter, Trans. R. Soc.…”
Section: Classes Of Agents and Clinical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-Waili reported over 90% efficacy in two studies in children (8,9). However, other studies in both pediatric and adult populations have not shown equal success but instead have shown effectiveness in 80% (211) and in 60% or less (39,92,132; L. di Martino, A. Nocerino, and M. Pettoello Mantovani, Letter, Trans. R. Soc.…”
Section: Classes Of Agents and Clinical Propertiesmentioning
confidence: 99%
“…Clinical trials have employed dosing two and three times daily (usually 250 mg/dose) for 5 to 10 days and shortcourse (1 to 3 days), daily single-dose therapy (2.0 or 2.4 g/ dose) (261). In the 5-to 10-day schedules the efficacy ranges from 60 to 100% in adult and pediatric patients, with a median efficacy in both groups of 92% (Table 1) (20,49,68,91,92,100,127,132,135,150,151,191,201,202,232,256). In general, this schedule is well tolerated, with most side effects involving gastrointestinal upset and metallic taste ( Table 2).…”
Section: Classes Of Agents and Clinical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation